Analysis of Emigration and Social Demographic Conditions on Divorce and Economic Levels in East Java - ZAMHIR, Zamhir; ASHAR, Khusnul; SATRIA, Dias (International Journal of Environmental, Sustainability, and Social Science, 2023)
Economic development is one of the essential pillars for the attainment of people’s wellbeing. Indonesia is one of the largest migrant worker contributors in southeast Asia, where East Java is its biggest supplier. However, the high number of migrant workers and the improving economic condition in the province are followed by the increasing number of divorce cases, which are interesting to study further. It has been widely believed that the driver for people to become migrant workers is the hope of having better economic opportunities. In fact, following the attainment, they have problems with their marriage, which lead to divorce. The objective of his research is to identify the effect of emigration and socio-demographic condition on divorce rate and economic level in East Java. The multiple linear regression and probit model analyses have led to findings that emigration positively and significantly affect divorce cases in East Java, that emigration does not significantly influence the economic status of the migrant workers, that divorce does not influence the economic gains of the workers in the short run, and that migrant workers who are older, male, and better in education have a significant influence on the income increase of migrant workers in East Java.